A Strategic Shift from Traditional Philanthropy to Modern Philanthropy - Insawan Putri, Azzahrah; Suseno, Priyonggo; Sriyana, Jaka (Institut Agama Islam Negeri Kendari, 2026)
This study aims to analyze the transformation strategy of Islamic philanthropy from a traditional approach to modern philanthropy in BAZNAS Kendari City and Dompet Dhuafa Southeast Sulawesi. This study departs from the fact that Islamic philanthropic practices at the local level still show dualism: on the one hand, there is a strengthening of governance, digitalization, and empowerment orientation; On the other hand, the charitable approach and direct relations of muzakki-mustahik remain dominant. The research uses a qualitative approach with a case study type. Data was collected through interviews, observations, and documentation, then analyzed using Oliver Williamson's four-level institutional framework and the Business Model Canvas (BMC). The results of the study show that BAZNAS Kendari City has undergone a relatively more established transformation at the level of institutional governance, characterized by legal legitimacy, auditing, reporting systems, and strengthening the principles of transparency and accountability. However, the transformation at the resource allocation level is still in the transition phase because productive empowerment is not yet fully optimal. In contrast, Dompet Dhuafa Southeast Sulawesi is more adaptive in digital fundraising, partnerships, and distribution flexibility, but still faces weaknesses in the aspects of SOPs and institutionalization of governance. The main challenges of the two institutions include low community zakat literacy, dominance of charity approaches, limited human resources, and funding patterns that are not stable and not flexible enough to support program development. This article emphasizes that the transformation of Islamic philanthropy is not enough to be interpreted as the digitization of fundraising, but must include institutional professionalization, system strengthening, financing diversification, and sustainable empowerment orientation